Probing the carbon-hydrogen activation of alkanes following photolysis of Tp’Rh(CNR)(carbodiimide): a computational and time-resolved infrared spectroscopic study - Guan, Jia; Wriglesworth, Alisdair; Brothers, Edward N.; Snežana, D. Zarić; Jones, William D.; Hall, Michael B.; George, Michael W. (American Chemical Society, 2017)
Carbon–hydrogen bond activation reactions of alkanes by Tp’Rh(CNR) (Tp’ = Tp = trispyrazolylborate or Tp* = tris(3,5-dimethylpyrazolyl)borate) were followed by timeresolved infrared spectroscopy (TRIR) in the υ(CNR) and υ(BH) spectral regions on Tp*Rh(CNCH2CMe3), and their reaction mechanisms were modelled by density functional theory on TpRh(CNMe). The major intermediate species were analogs of those in the previously studied Tp’Rh(CO) alkane activations: κ3-η1-alkane complex (1); κ2-η2-alkane complex (2); and κ3-alkyl hydride (3). Calculations predict that the barrier between 1 and 2 arises from a triplet-singlet crossing and leads to the singlet κ2-Tp’Rh(CNR)(η2-alkane) with one pyrazolyl arm dechelated, and a strongly bonded alkane. Intermediate 2 proceeds over the rate-determining C-H activation barrier to give the final product 3. The carbon hydrogenactivation lifetimes measured for the Tp*Rh(CNR) and Tp*Rh(CO) fragments with four cycloalkanes (C5H10, C6H12, C7H14, and C8H16) increase with alkanes size and show a dramatic increase between C6H12 and C7H14, indicating the control that the alkane has on the rate of C-H activation. Similar step-like behaviour was observed previously in studies on cycloalkane reactions with CpRh(CO) and Cp*Rh(CO) fragments and is attribute to the wider difference in C-H bonds that appear at C7H14. However, these rhodium fragments are significantly different in terms of their absolute lifetimes, as Tp’Rh(CNR) and Tp’Rh(CO) fragments have much slower rates of C-H activation and longer lifetimes compared to those of CpRh(CO) and Cp*Rh(CO) fragments. This is in accordance with reduced electron density in dechelated κ2-η2-alkane Tp’ complexes, which stabilizes the d8 Rh(I) in a square-planar geometry and weakens the metal's ability for oxidative addition of the C-H bond. Further, the Tp’Rh(CNR) fragment has significantly slower rates of C-H activation in comparison to the Tp’Rh(CO) fragment especially for the larger cycloalkanes. This behaviour can be attributed to steric bulk of the neopentyl isocyanide ligand, which hinders the rechelation in κ2- Tp’Rh(CNR)(cycloalkane) species and results in the C-H activation without the assistance of the rechelation. On the other hand, the C-H activation in κ2-Tp’Rh(CNR)(alkane) is assisted by CNR weaker backbonding, which increases electron density on metal centre in comparison to κ2-Tp’Rh(CO)(alkane).